Efectos de niveles de área foliar y dosis de ácido indolbutírico en el enraizamiento de Caoba (Swietenia macrophylla G. King) en cámaras de subirrigación - Gronerth Valdivieso, Carlos (2009)
The present study evaluated the effects of three levels of area leaf and four doses of indole-3-acid (AIB) on the ability rooting of cuttings of young mahogany (Swietenia macrophylla K.), using cameras subirrigation. The trial was conducted in Nursery Research Institute of the Peruvian Amazon in San Martin (IIAP), using a completely randomized design with factorial treatments consisting of twelve, eight and eight repetitions cuttings per experimental unit. After 60 days there was a 62,50% rooting of cuttings with 1 leaflet (180 cm2) and 0,4% of AIB. It is necessary, the use of shadow on the propagators for reduce the radiation and air temperatures within the substrate the propagators, as well as to maintain high relative humidity.